The Discursive Contradiction between Government Legitimacy and Labor Resistance: An Analysis of Fairclough's Critical Discourse on Two Perspectives of National Apprenticeship News in Kompas.com - Desyfa Cahya Aina; Sabrina Al Izzati; Siska Rakhmawati (Universitas Negeri Semarang, 2026)
This study aims to uncover the ideological dynamics and power relations in Kompas.com news about the National Apprenticeship Program using the Norman Fairclough model of Critical Discourse Analysis (CDA). The focus of the study is directed at two news texts that display the contradiction of representation between the legitimacy of the government and the resistance of labor unions, namely